Cluster Analysis Approach to Identify Rock Type in Tertiary Reservoir of Khabaz Oil Field Case Study - Al Kattan, Wafa; AL Jawad, Sameer N.; Jomaah, Haider Ashour (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
Rock type identification is very important task in Reservoir characterization in order to constrict robust reservoir models. There are several approaches have been introduced to define the rock type in reservoirs and each approach should relate the geological and petrophysical properties, such that each rock type is proportional to a unique hydraulic flow unit. A hydraulic flow unit is a reservoir zone that is laterally and vertically has similar flow and bedding characteristics. According to effect of rock type in reservoir performance, many empirical and statistical approaches introduced.  In this paper Cluster Analysis technique is used to identify the rock groups in tertiary reservoir for Khabaz oil field by analyses variation of petrophysical properties data that predicted by analysis of well log measurements.  In tertiary reservoir four groups identified by cluster analysis technique, were each group was internally similar in petrophysical properties and different from others groups.